Avaliação dos hábitos de higiene bucal e da eficácia da utilização de escovas convencional e elétrica por idosos de Centros de Convivência de Vitória-ES - Nobre, Cristiane Vasconcellos Cáspar (2009)
The aim of this research was to verify the health status and oral hygiene habits in elderly subjects frequenting Social Centers in Vitória, ES, and to compare the effectiveness of powered toothbrush to manual toothbrush. The sample constituted of 60 independent elderly subjects from both sex and presenting different oral status. They were randomly divided into two groups: EE – constituted of 30 subjects who received powered tooth brush; and EM – constituted of 30 subjects who received manual tooth brush for their oral hygiene. The DMF-T rate found was 23,93, is that 50% of teeth were missing, 2% decayed, 21% restored, and 24% sound. A 41% of the elderly subjects had edentulous maxilla or mandible and all of them worn full denture. The oral hygiene habits were satisfactory. All brushed the teeth with dentifrice, 65% twice or three times a day, only 28% used dental floss. Ninety-six percent of the elderly cleaned the dentures only with toothpaste, and 5% did not remember having instructions on oral hygiene. The results of the randomized, singleblind, and clinical prospective study on effectiveness of a electric toothbrush, Oral B Cross Action Power, showed that the plaque scores for 7-day and 15-day were 24,91 ± 12,81 and 22,11 ± 14,46, respectively, corresponding to a plaque removal of 50,24% for 7-day and 55,83% for 15-day. The results of manual toothbrush, Bitufo Class 32 soft, showed that plaque scores for 7-day and 15-day were 30,51 ± 13,85 and 24,31 ± 15,24, respectively, corresponding to 36,64% of plaque removal for 7- day and 49,51% for 15-day. Both powered and manual toothbrushes were effective in removing plaque after 7-day and 15-day relative to baseline. Although the powered toothbrush have removed more plaque than the manual toothbrush, theses results were not statistically significant. Based on the obtained results, it was concluded that the oral health status and oral hygiene habits performed by the studied elderly subjects were satisfactory. As for the effectiveness of powered toothbrushes versus the manual toothbrushes for elderly subjects, further research is needed.